-107-x=-9x+133

Simple and best practice solution for -107-x=-9x+133 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -107-x=-9x+133 equation:


Simplifying
-107 + -1x = -9x + 133

Reorder the terms:
-107 + -1x = 133 + -9x

Solving
-107 + -1x = 133 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-107 + -1x + 9x = 133 + -9x + 9x

Combine like terms: -1x + 9x = 8x
-107 + 8x = 133 + -9x + 9x

Combine like terms: -9x + 9x = 0
-107 + 8x = 133 + 0
-107 + 8x = 133

Add '107' to each side of the equation.
-107 + 107 + 8x = 133 + 107

Combine like terms: -107 + 107 = 0
0 + 8x = 133 + 107
8x = 133 + 107

Combine like terms: 133 + 107 = 240
8x = 240

Divide each side by '8'.
x = 30

Simplifying
x = 30

See similar equations:

| 0=16t^2-27t-10 | | 8c-5-c=51 | | 1y+27=9y+19 | | 3d-.4=11 | | -100-6x=170+3x | | Y+27=9y+19 | | Y=0.20x+134 | | -1+x=-2+y | | 3a-8=9a-74 | | Y=0.90x+134 | | -2m-6+19+(-4m)+9= | | Y^2+8y=-12 | | -1+x=-1+y | | -5+m=10 | | 10s-96=5s-36 | | 6*a=33 | | 2x^2+10x-256=0 | | 4.5b-5.25+3=3.75 | | 6u-97=3u-40 | | X^2+17s+c=0 | | 4-6x-3(2x+5x)= | | -31=3y+9-8v | | Y=650-50x | | 9x-100=3x+26 | | 2m=-5 | | 3z-1=7z-17 | | 2X=6z+3y-1 | | X=6z+3y-1 | | 3n+4n=3n+6 | | -9x-88=2x+176 | | 4z+2y-1=X | | 4y+2y-1=X |

Equations solver categories